Penerapan Terapi Relaksasi Nafas Dalam Dan Memukul Bantal Pada Pasien Dengan Perilaku Kekerasan Di Ruang Rawat Inap - Firdawati Ella Febrianti; Ira Ocktavia Siagian (Jurnal Kesehatan, 2025)
Violent behavior in patients with mental disorders, particularly schizophrenia, is a serious health issue whose prevalence continues to rise in Indonesia, especially in West Java. Schizophrenia often triggers violent behavior due to the distortion of reality, hallucinations, or delusions experienced by the patient. Deep breathing relaxation therapy and pillow punching have proven effective as non-pharmacological interventions to help manage anger, reduce tension, and provide a sense of calm, unlike pharmacological therapy which can have side effects such as drowsiness or drug dependence. This research aims to analyze the effectiveness of the therapy on patients with violent behavior at the West Java Provincial Mental Hospital. This research using case study method involved data collection through interviews and observations of 3 research subjects. The implementation carried out over 4 days aimed to reduce the intensity of violent behavior in patients. The research results indicate a significant decrease in the intensity of violent behavior in patients Mr. A.B and Mr. D.A, while Mr. A.A still requires additional intervention. This decrease is due to the therapy's ability to help patients manage negative emotions. Factors of non-compliance with medication have also been found to contribute to violent behavior that occurs. Researchers emphasize the importance of implementing this therapy as part of a comprehensive violence management strategy, with support from family and healthcare professionals. This research is expected to strengthen the application of non-pharmacological therapy in mental health care protocols and provide a foundation for further studies comparing the effectiveness of pharmacological and non-pharmacological therapies.